Using Indigenous Science to Protect Wetlands: The Swinomish Tribe’s Wetland Cultural Assessment - Todd A. Mitchell; Nicole J. Casper; Lindsay Thomason Logan; Erin M. Colclazier; Karen J. R. Mitchell (Ethnobiology Letters, 2025)
While wetland functional assessment or rating systems may include cultural, socioeconomic, or site value components, they are insufficient to evaluate the cultural functions of wetlands to resource-centric communities like Native Nations. The Swinomish Indian Tribal Community has developed a cultural module for use in conjunction with standard physical wetland assessment approaches to incorporate Tribal cultural values and functions in wetland rating. The Swinomish cultural module leverages traditional plant use data from historical and community sources to create a comprehensive plant list and database and identify evaluation categories for assessment. Six categories were used: four use-based categories (construction/household uses, medicinal uses, subsistence uses, and spiritual/ceremonial uses), and two weighting categories (common use, plant rarity). Botanical surveys of fourteen wetlands produced a botanical inventory that was compared to the list of traditionally used plants. Each wetland was given a cultural module score and cultural value rating based on the number of species of traditional use plants observed. Wetlands for which surveys were not available were evaluated for similarity to surveyed wetlands and assigned scores from the most similar. The cultural module score is used in combination with traditional physical functional rating systems to produce a robust, culturally relevant, overall wetland rating. The Swinomish cultural module was designed to be easy to use and update as additional cultural plant data or wetland site data become available or physical functional assessment methods change. The resultant wetland ratings are used in regulating land-use to protect wetland function, both physical and cultural.